Circuit board and manufacturing method thereof
By irradiating the insulating layer with UV laser, small-diameter through holes is formed, and dry-type slag removal treatment is used to solve the problem of the through hole opening diameter deviation from the design value and wet-type slag removal treatment, and high-quality copper plating layer formation is achieved and low manganese content insulating layer.
Patent Information
- Application Number
- CN202380049745.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when forming an insulating layer with small diameter through-holes, the opening diameter of the through-holes is prone to deviate from the design value, making it difficult to form a high-quality copper plating layer. At the same time, wet removal using strong oxidants such as potassium permanganate aqueous solution is also required. Glue slag treatment leads to environmental and cost problems.
By irradiating the insulating layer with specific UV laser light, small diameter through holes are formed, and dry-type glue removal treatment is performed between the through hole formation step and the copper plating layer formation step to avoid the use of strong oxidants.
The small diameter through holes is formed according to the design value, which reduces the amount of glue slag generated in the through holes, avoids wet removal treatment, reduces the manganese content of the insulating layer, and increases the adhesion between the insulating layer and the copper-plated layer. sex.
Smart Images

Figure CN119452738A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a circuit board, and more particularly to a circuit board including an insulating layer having a through hole formed therein. In addition, the present invention relates to a method for manufacturing a circuit board including an insulating layer. Background Art
[0002] In recent years, circuit substrates widely used in various electronic devices require miniaturization and high-density circuit wiring for miniaturization and high-functionality of electronic devices. As a manufacturing technology for circuit substrates, a build-up method of alternately stacking insulating layers and conductive layers on a substrate is known.
[0003] In the manufacturing method of the build-up method, for example, the insulating layer is formed by thermally curing a resin layer provided on a support. Then, the formed insulating layer is drilled by laser irradiation to form a through hole, and a wet desmearing process is performed to remove the resin residue (smear) inside the through hole and roughen the surface of the insulating layer. Then, after the desmearing process, a copper plating process is performed to attach copper plating inside the through hole (for example, refer to Patent Document 1).
[0004] However, when forming a through hole by laser irradiation as described in patent documentation 1, due to the generation of smear, a wet desmearing process for removing a large amount of smears must be carried out. In wet desmearing, a method using strong oxidants such as potassium permanganate aqueous solution is generally adopted. However, potassium permanganate aqueous solution is a highly toxic substance, and it is a substance that is desired to be avoided from the viewpoint of environmental restrictions and cost. Therefore, in order to avoid adopting the wet desmearing process for removing smear, a through hole forming method that develops a generation amount of smears that can reduce becomes a technical problem that needs to be solved.
[0005] In order to reduce the amount of slag generated by the above-mentioned technical problems, it has been proposed to use CO 2 There is a method of forming a through hole by laser irradiation (see, for example, Patent Document 2).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-294873
[0009] Patent Document 2: Japanese Patent Application Publication No. 9-107167 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] However, as described in Patent Document 2, 2When a through hole with a small diameter is formed by laser irradiation, a new technical problem that needs to be solved is that the opening diameter of the through hole deviates from the designed value. As a result, it is difficult to form a copper plating layer on the insulating layer having the through hole with a small diameter.
[0012] Technical solutions used to solve technical problems
[0013] The inventors of the present invention have conducted in-depth research on the above technical problems and found that by subjecting the insulating layer to specific UV laser irradiation, a through hole with a small diameter can be formed according to the designed value, and the amount of smear generated in the through hole can be reduced. As a result, since a wet desmear treatment using a strong oxidant such as potassium permanganate aqueous solution is not required, the manganese content of the insulating layer can be reduced. The inventors of the present invention have completed the invention based on the above findings.
[0014] That is, the circuit substrate according to the first embodiment of the present invention is a circuit substrate including an insulating layer having a through hole formed therein, characterized in that:
[0015] The insulating layer is composed of a cured product of a thermosetting resin composition, wherein the thermosetting resin composition comprises a thermosetting resin and an inorganic filler.
[0016] The opening diameter of the top of the through hole is 30 μm or less,
[0017] The manganese content of the insulating layer is less than 50 ppm.
[0018] In the first embodiment of the present invention, it is preferred that the copper plating layer is formed on at least a portion of the insulating layer, and the peel strength between the insulating layer and the copper plating layer is 2.5 N / cm or more.
[0019] In the first embodiment of the present invention, it is preferred that the arithmetic mean roughness of the insulating layer is less than 150 nm.
[0020] In the first embodiment of the present invention, it is preferred that the opening diameter of the top of the through hole is 20 μm or less.
[0021] In the first embodiment of the present invention, it is preferred that the thermosetting resin includes polyphenylene ether.
[0022] A method for manufacturing a circuit board according to a second embodiment of the present invention, wherein the circuit board includes an insulating layer, is characterized by comprising:
[0023] The step of irradiating the insulating layer with a pulse laser having a wavelength of not less than 200 nm and not more than 400 nm and a pulse width of not more than 20 nanoseconds at an output power of not less than 0.3 W to form a through hole;
[0024] A step of performing copper plating on the through hole without performing a wet desmear process using a strong oxidant to form a copper plated layer.
[0025] In the second embodiment of the present invention, it is preferred that the pulse width of the pulse laser is less than 1 nanosecond.
[0026] In the second embodiment of the present invention, it is preferred that the wavelength of the pulse laser be 300 nm or less.
[0027] In the second embodiment of the present invention, it is preferable that a dry desmear step is performed between the step of forming the through hole and the step of forming the copper plating layer.
[0028] In the second embodiment of the present invention, it is preferred that the copper plating layer is formed on at least a portion of the insulating layer, and the peel strength between the insulating layer and the copper plating layer is 2.5 N / cm or more.
[0029] In the second embodiment of the present invention, it is preferred that the arithmetic mean roughness of the insulating layer is less than 150 nm.
[0030] In the second embodiment of the present invention, it is preferred that the opening diameter of the top of the through hole is 30 μm or less.
[0031] Advantageous Effects of the Invention
[0032] According to the present invention, since a through hole with a small diameter can be formed according to the design value, and the amount of smear generated in the through hole is reduced, it is not necessary to perform a wet desmear treatment using a strong oxidant such as a potassium permanganate aqueous solution, and a circuit substrate with a reduced manganese content in the insulating layer can be provided. Furthermore, the circuit substrate of the present invention can provide good adhesion between the insulating layer and the copper plating layer. In addition, according to another embodiment of the present invention, a method for manufacturing a circuit substrate using specific UV laser irradiation can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic cross-sectional view showing one embodiment of a circuit board according to the present invention. DETAILED DESCRIPTION
[0034] [Circuit board]
[0035] The circuit substrate of the present invention has an insulating layer having a through hole. The shape of the through hole is not particularly limited, but is generally roughly circular. The through hole can be a full through hole, a blind hole, or a buried hole. The circuit substrate of the present invention is described with reference to the accompanying drawings. Figure 1 It is a schematic cross-sectional view showing a circuit substrate. Figure 1The circuit board 1 shown has an insulating layer 3 on a substrate 2 and a through hole 4 formed in the insulating layer 3. Here, the opening diameter of the top of the through hole 4 is represented by Φt, and the opening diameter of the bottom of the through hole 4 is represented by Φb. In addition, the opening diameter Φb of the bottom of the through hole 4 refers to the opening diameter of the substrate 2 side of the through hole 4, and the opening diameter Φt of the top of the through hole 4 refers to the opening diameter on the side opposite to the substrate side of the through hole 4. In addition, the circuit board 1 has a copper plating layer (not shown) on the insulating layer.
[0036] The opening diameter Φt of the top of the through hole can be formed to be 30 μm or less, preferably 25 μm or less, more preferably 20 μm or less, further more preferably 18 μm or less, and most preferably 15 μm or less according to the design value by using a specific UV laser described in detail below. In addition, the opening diameter Φb of the bottom of the through hole is preferably 30 μm or less, more preferably 25 μm or less, and further preferably 15 μm or less.
[0037] The depth from the top to the bottom of the through hole is not particularly limited, but is, for example, preferably 5 μm to 35 μm, more preferably 8 μm to 30 μm, and further preferably 10 μm to 25 μm.
[0038] Furthermore, since it is possible to reduce the CO 2 To avoid the inconvenience caused by heat processing caused by laser, it is preferable to use a specific UV laser as described in detail below.
[0039] [Base material]
[0040] As the base material of the circuit substrate, in addition to printed wiring boards or flexible printed wiring boards with circuits pre-formed with copper or the like, there are copper-clad laminates of all grades (FR-4 grade) such as copper-clad laminates for high-frequency circuits using paper phenolic resin, paper epoxy resin, glass cloth epoxy resin, glass polyimide, glass cloth / non-woven fabric epoxy resin, glass cloth / paper epoxy resin, synthetic fiber epoxy resin, fluororesin·polyethylene·polyphenylene ether, polyphenylene ether·cyanate ester, etc. In addition, metal substrates, polyimide films, PET films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, chip boards, etc. can also be listed.
[0041] [Insulation layer]
[0042] The insulating layer is composed of a cured product of a thermosetting resin composition, and the thermosetting resin composition includes a thermosetting resin and an inorganic filler. In addition, the manganese content of the insulating layer is less than 50 ppm, preferably less than 30 ppm, more preferably less than 20 ppm, and further preferably less than 10 ppm. If the manganese content of the insulating layer is lower than the above value, it is preferred not to perform a wet desmear treatment using a strong oxidant such as an aqueous potassium permanganate solution from the viewpoint of environmental restrictions and cost.
[0043] In the present invention, the manganese content of the insulating layer is the amount of manganese quantified by the following method. On a circuit substrate after forming through holes and performing various desmear treatments, 50 mg of the insulating layer is cut off with a cutter and weighed, and then placed in 100 ml of ultrapure water and boiled for 30 minutes, and the liquid subjected to ultrasonic waves for 30 minutes is filtered and the volume is measured. Then, the amount of manganese can be quantified by ICP emission spectrometry using a polytype ICP emission spectrometer 720ICP-OES (manufactured by Agilent Technologies, Inc.).
[0044] The cured product in the present invention refers to a state in which a waste cloth containing isopropyl alcohol is placed on the surface of the cured thermosetting resin composition, a 500 g weight is placed thereon and left to stand for 1 minute, and the thermosetting resin composition is not attached to the surface of the waste cloth.
[0045] The copper-plated layer is preferably formed on at least a portion of the insulating layer without undergoing a wet desmear treatment. The copper-plated layer is formed on at least a portion of the insulating layer, and the peel strength between the insulating layer and the copper-plated layer is preferably 2.5 N / cm or more, more preferably 3.0 N / cm or more, further preferably 4.0 N / cm or more, and further more preferably 5.0 N / cm or more. If the peel strength is above the above value, it can be said that the insulating layer and the copper-plated layer have excellent adhesion.
[0046] In the present invention, the peel strength between the insulating layer and the copper-plated layer formed on at least a portion of the insulating layer is a value measured by peeling off a 35 mm long copper-plated layer cut out of a rectangle having a width of 10 mm (short side) and a length of 60 mm (long side) from the insulating layer at an angle of 90 degrees and a speed of 50 mm / min using a table-top tensile tester (EZ-SX manufactured by Shimadzu Corporation).
[0047] The arithmetic mean roughness of the insulating layer is preferably 10 nm or more and 150 nm or less, more preferably 15 nm or more and 125 nm or less, and further preferably 20 nm or more and 100 nm or less. If the arithmetic mean roughness of the insulating layer is within the above numerical range, the adhesion to the copper plating layer is good, and the yield rate in the manufacturing process is good, and the productivity is good.
[0048] [Thermosetting resin composition]
[0049] Thermosetting resin compositions are used to form an insulating layer on a substrate. Thermosetting resin compositions contain a thermosetting resin and an inorganic filler, and may further contain a curing agent, a solvent, and the like.
[0050] (Thermosetting resin)
[0051] As the thermosetting resin, a resin having a functional group capable of undergoing a curing reaction by heat can be used. Examples of the thermosetting resin include: polyphenylene ether, isocyanate compounds, blocked isocyanate compounds, amino resins, maleimide compounds, benzoxazine resins, carbodiimide resins, cyclocarbonate compounds, epoxy resins, oxetane compounds, episulfide resins, phenoxy resins and other commonly known resins. The thermosetting resin can be used alone or in combination of two or more. As the thermosetting resin, polyphenylene ether, epoxy resin and phenoxy resin are preferred, and polyphenylene ether is more preferred.
[0052] As the polyphenylene ether, any structure can be used, but preferably a structure containing a crosslinkable functional group. In addition, among the crosslinkable functional groups, the structure after crosslinking is preferably a functional group structure with low loss in the high-frequency region above 1 GHz. As such functional groups, unsaturated double bonds, cyano groups, dicyano groups, epoxy groups, etc. can be listed. The functional group content is not particularly limited, and is preferably within a range that does not significantly change the electrical properties of the original polyphenylene ether, and contains an amount that forms an effective crosslinked structure. The molar ratio is preferably less than 50%, more preferably less than 25%, preferably more than 3%, and further preferably more than 6%. The upper limit of the molecular weight is preferably less than 300,000 in terms of weight-average molecular weight (Mw), and more preferably less than 100,000. The lower limit is preferably more than 1000, and more preferably more than 5000. These polyphenylene ethers can be used alone or in combination of two or more.
[0053] The epoxy resin is a compound having an epoxy group, and any conventionally known epoxy resin may be used, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, brominated bisphenol A epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, bisphenol A novolac epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, dicyclopentadiene epoxy resin, triphenylmethane epoxy resin, etc. These epoxy resins may be used alone or in combination of two or more.
[0054] Examples of commercially available epoxy resins include jER828, 806, 807, YX8000, YX8034, and 834 manufactured by Mitsubishi Chemical Corporation, YD-128, YDF-170, ZX-1059, and ST-3000 manufactured by Nippon Steel Chemicals Co., Ltd., EPICLON830, 835, 840, 850, N-730A, and N-695 manufactured by DIC Corporation, and NC3000H and RE-306 manufactured by Nippon Kayaku Co., Ltd.
[0055] As phenoxy resin, there is no particular limitation as long as it is a condensate of epichlorohydrin and various bifunctional phenol compounds. As commercially available phenoxy resins, there can be cited: FX280 and FX293 manufactured by Nippon Steel Chemical Materials Co., Ltd., YX6950BH30, YX8100, YX6954, YL6954, and YL6974 manufactured by Mitsubishi Chemical Corporation. The phenoxy resin can be used alone or in combination of two or more.
[0056] (Curing agent)
[0057] As the curing agent, a known curing agent that is usually used to cure the above-mentioned thermosetting resin can be used, for example, phenolic resin, polycarboxylic acid and its anhydride, cyanate resin, active ester resin, maleimide compound, alicyclic olefin polymer, amine, imidazoles, etc. can be listed. One kind of curing agent can be used alone, or two or more kinds can be used in combination. As the curing agent, phenolic resin, active ester resin, imidazoles are preferably used.
[0058] Examples of the phenolic resin include phenol novolac resins, alkylphenol novolac resins, bisphenol A novolac resins, dicyclopentadiene-type phenolic resins, Xylok-type phenolic resins, terpene-modified phenolic resins, cresol / naphthol resins, polyvinylphenols, phenol / naphthol resins, phenolic resins containing an α-naphthol skeleton, and cresol novolac resins containing triazine.
[0059] Active ester resin is a resin having two or more active ester groups in one molecule. Active ester resin can be generally obtained by condensation reaction of carboxylic acid compound and hydroxyl compound. Among them, active ester compound obtained by using phenol compound or naphthol compound as hydroxyl compound is preferred. As phenol compound or naphthol compound, hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadienyl diphenol, phenol novolac, etc. can be cited.
[0060] Examples of imidazoles include reaction products of epoxy resins and imidazoles, and specifically include 2-methylimidazole, 4-methyl-2-ethylimidazole, 2-phenylimidazole, 4-methyl-2-phenylimidazole, 1-benzyl-2-methylimidazole, 2-ethylimidazole, 2-isopropylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, and 1-cyanoethyl-2-undecylimidazole. Examples of commercially available imidazoles include 2E4MZ, C11Z, C17Z, and 2PZ (reaction products of epoxy resin and imidazole), 2MZ-A, 2E4MZ-A, and 2MZA-PW (AZINE compounds of imidazole), 2MZ-OK and 2PZ-OK (isocyanurates of imidazole), and 2PHZ and 2P4MHZ (hydroxymethyl imidazole) (all manufactured by Shikoku Chemicals Co., Ltd.). Examples of commercially available imidazole latent curing agents include Curesol P-0505 (manufactured by Shikoku Chemicals Co., Ltd.).
[0061] (Inorganic filler)
[0062] As the inorganic filler, known inorganic fillers can be used, preferably: barium sulfate, spherical silica, hydrotalcite and talc. They can be used alone or in combination of two or more. As the inorganic filler, spherical silica is particularly preferably used.
[0063] As spherical silica, any spherical silica that can be used as a filler for electronic materials can be used. The shape of the spherical silica is spherical, and is not limited to the shape of a sphere. As a preferred spherical silica, for example, spherical silica having a sphericity of 0.8 or more as measured below can be cited, but it is not limited thereto.
[0064] The sphericity is determined as follows. That is, first, a photograph of spherical silica is taken using a scanning electron microscope (SEM), and the area and circumference of the particles observed in the photograph are used as (sphericity) = {4π×(area)÷(circumference) 2 Specifically, the average value of 100 particles measured using an image processing device can be used.
[0065] The average particle size of spherical silica is not particularly limited, and is preferably 0.05 to 10 μm, more preferably 0.1 to 5 μm, and further preferably 0.3 to 1 μm. The average particle size of spherical silica refers to an average particle size (D50) that includes not only the particle size of primary particles but also the particle size of secondary particles (agglomerates), and is the value of D50 measured by laser diffraction. As a measuring device using laser diffraction, Microtrac MT3300EXII manufactured by Mechik Baier Co., Ltd. can be cited. In addition, the maximum particle size (D100) and the particle size (D10) can also be measured in the same manner in the above-mentioned device. In addition, the average particle size of the spherical silica contained in the resin layer of the present invention refers to the value measured as described above of the spherical silica before adjusting (pre-stirring, mixing) the thermosetting resin composition that forms the insulating layer.
[0066] The inorganic filler may also be subjected to surface treatment. As the surface treatment, surface treatment without introducing organic groups such as surface treatment using a coupling agent or alumina treatment may also be performed. The surface treatment method of the inorganic filler is not particularly limited, and a known and commonly used method may be used, and the surface of the inorganic filler may be treated with a surface treatment agent having a curable reactive group, such as a coupling agent having a curable reactive group as an organic group.
[0067] The surface treatment is preferably a surface treatment performed using a coupling agent. As a coupling agent, coupling agents such as silane, titanate, aluminate and zirconium aluminate can be used. Among them, a silane coupling agent is preferred. As examples of the silane coupling agent involved, vinyl trimethoxysilane, vinyl triethoxysilane, N-(2-aminomethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-anilinopropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, etc. can be listed. They can be used alone or in combination.
[0068] Based on the total amount of the thermosetting resin composition constituting the insulating layer, the amount of the inorganic filler in the insulating layer is preferably 20 to 80% by mass, more preferably 35 to 75% by mass. By keeping the amount of the inorganic filler within the above range, the excessive increase in viscosity of the thermosetting resin composition can be suppressed, and good coating and molding properties can be maintained. In addition, the cured product can have sufficient strength.
[0069] [Dry film]
[0070] When forming the insulating layer, the above-mentioned thermosetting resin composition can also be used in the form of a dry film. The dry film includes a first film and a thermosetting resin layer that is releasably provided on one surface of the first film, and can also include a second film that is releasably provided on the surface of the thermosetting resin layer. Here, the first or second film and the thermosetting resin layer can be peeled off, which means that the first or second film and the thermosetting resin layer can be peeled off (i.e., excellent peelability) by normal operation (without applying excessive force) and without damaging the first or second film and the thermosetting resin layer.
[0071] (First film)
[0072] The first film plays a role as a support of the thermosetting resin layer. The thermosetting resin layer refers to a layer that is at least bonded to the thermosetting resin layer when it is laminated and integrally formed by heating in a manner that is in contact with a base material such as a substrate. The first film can be peeled off from the thermosetting resin layer in a process after lamination of the base material and the thermosetting resin layer. The first film is preferably peeled off from the thermosetting resin layer (insulating layer) in a process after curing the thermosetting resin layer.
[0073] As the first film, any known film can be used without particular limitation, and for example, a film made of thermoplastic resins such as polyester film such as polyethylene terephthalate or polyethylene naphthalate, polyimide film, polyamide-imide film, polypropylene film, polystyrene film, etc. can be preferably used. Among them, from the viewpoints of heat resistance, mechanical strength, operability, etc., polyester film is preferred, and polyethylene terephthalate film is particularly preferred. In addition, a laminate of these films can also be used as the first film.
[0074] The thickness of the first film is not particularly limited, and may be, for example, 10 μm to 150 μm.
[0075] (Second film)
[0076] After forming the thermosetting resin layer on the first film, it is preferred to laminate a peelable second film on the surface of the thermosetting resin layer for the purpose of preventing dust from adhering to the surface of the resin layer. The so-called second film refers to a film that is peeled off from the thermosetting resin layer before lamination when the thermosetting resin layer side of the dry film is laminated with a base material such as a substrate in contact with each other by heating or the like to form an integral body.
[0077] As the second film, for example, polyethylene film, polytetrafluoroethylene film, polypropylene film, surface-treated paper, etc. In the present invention, when the second film is peeled off, the adhesion between the resin layer and the second film is smaller than the adhesion between the thermosetting resin layer and the first film.
[0078] The thickness of the second film is not particularly limited, and may be, for example, 10 μm to 150 μm.
[0079] In addition, in the present invention, a thermosetting resin layer may be formed by coating a thermosetting resin composition on the second film and drying it, and the first film may be laminated on the surface thereof. That is, as the film coated with the thermosetting resin composition when manufacturing the dry film of the present invention, any one of the first film and the second film may be used.
[0080] [Method for manufacturing circuit board]
[0081] The manufacturing method of the circuit substrate with an insulating layer of the present invention comprises a through-hole forming step and a copper-plated layer forming step. In the present invention, since the amount of smear generated can be reduced in the through-hole forming step, a wet desmearing step using a strong oxidant can be avoided before the copper-plated layer forming step. Furthermore, the manufacturing method of the circuit substrate with an insulating layer of the present invention preferably performs a dry desmearing step between the through-hole forming step and the copper-plated layer forming step.
[0082] (Through-hole forming process)
[0083] In the through-hole forming process, a specific pulse laser is irradiated on the insulating layer of the substrate to form the through-hole. The pulse laser has the following features 1 to 3, which can suppress the amount of smear generated, and even if the opening diameter of the through-hole is small, it can be formed according to the designed value.
[0084] (feature)
[0085] 1. Wavelength
[0086] The wavelength of the pulsed laser is 200 nm to 400 nm, preferably 200 nm to 360 nm, more preferably 200 nm to 320 nm, and further preferably 200 nm to 280 nm. If it is within the above range, it corresponds to the absorption band of the aromatic ring or unsaturated bond contained in the insulating layer of the present invention, so the through hole can be formed more effectively.
[0087] 2. Pulse width
[0088] The pulse width of the pulse laser is 20 nanoseconds or less, preferably 15 nanoseconds or less, more preferably 10 nanoseconds or less, further preferably less than 1 nanosecond, and preferably 1 picosecond or more.
[0089] 3. Output power
[0090] The output power of the pulse laser is 0.3 W or more, preferably 1 W or more, more preferably 5 W or more, and preferably 20 W or less.
[0091] (Dry desmearing process)
[0092] In the dry desmearing process, by performing dry desmearing on the insulating layer with the through hole, the surface of the insulating layer can be roughened while removing the smear. As a result, the adhesion between the insulating layer and the copper plating layer can be improved. Examples of dry desmearing include plasma etching under vacuum or atmospheric pressure, UV treatment, etc.
[0093] (Copper plating layer formation step)
[0094] The step of forming the copper plating layer is not particularly limited, and the copper plating layer can be formed on the inner wall of the through hole by a conventionally known method. According to a preferred embodiment of the present invention, the copper plating layer can be formed by electrolytic copper plating after the insulating layer is subjected to electroless copper plating.
[0095] [Example]
[0096] Next, the present invention will be described in further detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, the following "parts" and "%" are all based on mass unless otherwise specified.
[0097] <Synthesis of branched polyphenylene ether (PPE)>
[0098] 2.6 g of di-μ-hydroxybis[(N,N,N',N'-tetramethylethylenediamine)copper(II)] chloride (Cu / TMEDA) and 3.18 mL of tetramethylethylenediamine (TMEDA) were added to a 3 L two-necked eggplant flask, and the mixture was fully dissolved, and oxygen was supplied at 10 ml / min. The raw material phenols, i.e., 105 g of 2,6-dimethylphenol and 13 g of 2-allylphenol, were dissolved in 1.5 L of toluene to prepare a raw material solution. The raw material solution was added dropwise to the flask, and the mixture was reacted at 40°C for 6 hours while being stirred at a rotation speed of 600 rpm. After the reaction was completed, the mixture was reprecipitated with a mixed solution of 20 L of methanol: 22 mL of concentrated hydrochloric acid, filtered out, and dried at 80°C for 24 hours to obtain a branched polyphenylene ether (PPE).
[0099] The number average molecular weight of branched PPE is 20,000, and the weight average molecular weight is 60,000. The slope of the conformation diagram of branched PPE is 0.31. In addition, the number average molecular weight (Mn) and weight average molecular weight (Mw) of branched PPE are obtained by gel permeation chromatography (GPC). In GPC, Shodex K-805L is used as a chromatographic column, the column temperature is 40°C, the flow rate is 1 mL / min, the eluent is chloroform, and the standard substance is polystyrene.
[0100] <Preparation of Thermosetting Resin Compositions 1 and 2>
[0101] The components shown in the following Table 1 were mixed and stirred sufficiently. Then, the mixture was kneaded using a three-roll mill to prepare thermosetting resin compositions 1 and 2. The numerical values in Table 1 represent parts by mass.
[0102] <Preparation of Thermosetting Resin Composition 3>
[0103] 122 parts by mass of PMA (propylene glycol monomethyl ether acetate) was added to 100 parts by mass of branched PPE and 49 parts by mass of styrene elastomer (Asahi Kasei Corporation: trade name "Tuftec H1051"), mixed at 40°C for 30 minutes, and stirred to completely dissolve. 60 parts by mass of diallyl phthalate (manufactured by Tokyo Chemical Industry Co., Ltd.), 560 parts by mass of spherical silica filler (manufactured by Yaduma Co., Ltd.: trade name "SC2050-HNF"), and 16 parts by mass of maleimide resin (manufactured by DMI: trade name "BMI-3000J", Mw=3000) were added to the PPE resin solution thus obtained, respectively, and these were mixed and dispersed using a three-roll mill. Finally, 4 parts by mass of 1,4-bis-tert-butylperoxyisopropylbenzene (manufactured by NOF Corporation: trade name “PERBUTYL P-40”) was mixed as a peroxide, and the mixture was stirred with a magnetic stirrer to prepare a thermosetting resin composition 3 .
[0104]
Table 1
[0105]
[0106]
[0107] In addition, *1 to *12 in Table 1 represent the following compounds, respectively.
[0108] *1: Bisphenol A epoxy resin (manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 189)
[0109] *2: Dicyclopentadiene epoxy resin (manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 254 g / eq, softening point 74°C)
[0110] *3: Phenoxy resin (Mitsubishi Chemical Corporation, solid content 30% by mass, cyclohexanone / methyl ethyl ketone diluted product)
[0111] *4: Branched PPE synthesized above
[0112] *5: Phenolic resin (manufactured by Meiwa Chemicals Co., Ltd.)
[0113] *6: Active ester compound (manufactured by DIC Corporation, active ester equivalent 223 g / eq, solid content 65% by mass, toluene-diluted product)
[0114] *7: 2-Ethyl-4-methylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd.)
[0115] *8: Spherical silica (manufactured by Yaduma Co., Ltd., average particle size 0.5 μm)
[0116] *9: Spherical silica slurry (manufactured by Yaduma Co., Ltd.)
[0117] *10: 1,4-di-tert-butylperoxyisopropylbenzene (manufactured by NOF Corporation)
[0118] *11: Styrene elastomer (manufactured by Asahi Kasei Corporation)
[0119] *12: Maleimide resin (manufactured by DMI, weight average molecular weight 3000)
[0120] <Dry film production>
[0121] Thermosetting resin compositions 1 to 3 were coated on one side of a first film (38 μm thick, PET, manufactured by Toyobo Co., Ltd.: trade name "TN-200") using a bar coater, with the amount of solvent adjusted so that the viscosity was 0.5 to 20 dPa·s (25°C), and the film thickness after drying was 20 μm. Next, the film was dried at 100°C for 5 to 10 minutes in a hot air circulation drying oven until the amount of residual solvent in the thermosetting resin layer was 0.5 to 2.5% by mass, to prepare dry films 1 to 3 having a thermosetting resin layer on the first film. The viscosity is a 30-second value measured at 25° C. and a rotor rotation speed of 5.0 rpm using a cone-plate rotational viscometer (cone-plate type) (manufactured by Toki Sangyo Co., Ltd., TVE-33H, rotor 3°×R9.7) in accordance with JIS-Z8803:2011, specifically, JIS-Z8803:201110 “Method for measuring viscosity using a cone-plate rotational viscometer”.
[0122] <Production of Circuit Board with Insulating Layer>
[0123] For a double-sided printed wiring board with a copper thickness of 15 μm and a circuit having a thickness of 0.4 mm, MECetchBOND CZ-8100 (manufactured by MECetch Co., Ltd.) was used to roughen the copper surface. Next, a double-chamber vacuum laminator CVP-600 (manufactured by Nikko-Materials Co., Ltd.) was used to adhere the above-made dry films 1 to 2 to the circuit substrate after the roughening treatment using a laminator at a temperature of 80 to 110°C and a pressure of 0.5 MPa. Next, hot pressing was performed at a temperature of 80 to 110°C and a pressure of 0.5 MPa. Then, the insulating layer was cured by heating at 100°C for 30 minutes in a hot air circulation drying furnace and then at 180°C for 30 minutes. Then, the first film was peeled off to make a circuit substrate with an insulating layer.
[0124] When using dry film 3, the production was carried out under the same conditions as when using dry films 1 and 2, except that the lamination temperature and the heat pressing temperature were changed to 140°C, respectively, and the curing temperature by heating was changed to 200°C.
[0125] <Through hole formation using laser>
[0126] The insulating layer of each circuit board produced above was irradiated with laser light under the following conditions 1 to 5 to form a substantially circular through hole with a design value of the opening diameter of the top of the through hole being 30 μm, 20 μm or 15 μm.
[0127] (Laser conditions)
[0128] Condition 1: UV laser (wavelength 355nm), output power 0.4W, pulse width 17ns
[0129] Condition 2: UV laser (wavelength 266nm), output power 8W, pulse width 15ns
[0130] Condition 3: UV laser (wavelength 266nm), output power 8W, pulse width 15ps
[0131] Condition 4: CO 2 Laser, output power 0.6W, pulse width 20μs
[0132] [Measurement of through-hole opening diameter by SEM]
[0133] The opening diameter of the top of the through hole of the circuit substrate manufactured above is measured by image analysis of the image obtained by FE-SEM observation. The measurement conditions of the SEM image are as follows. The opening diameter of the top of each through hole formed relative to the design values described in Table 1 is evaluated using the following benchmarks, and the evaluation results are shown in Tables 2 to 4. In addition, if the evaluation is "◎" or "○", it is qualified. In addition, in Table 4, the measured values of the opening diameter of the top of Examples 9 to 11 are recorded in the lower section. In addition, in each evaluation, 10 through holes of the circuit substrate are arbitrarily selected for measurement, and the average value is used as the opening diameter of the through hole.
[0134] (SEM conditions)
[0135] Measuring device: FE-SEM SU5000 manufactured by Hitachi High-Technologies Corporation
[0136] Measurement conditions: Acceleration voltage 5.0 kV
[0137] Measurement mode: COMPO image (reflected electron composition image)
[0138] (Evaluation criteria for through holes)
[0139] ◎: The opening diameter of the top portion can be opened within a range of less than ±20% of the design value.
[0140] ○: The opening diameter of the top portion can be opened within ±20 to ±30% of the design value.
[0141] ×: The opening diameter of the top portion deviates by more than ±30% from the designed value.
[0142]
Table 2
[0143]
[0144]
Table 3
[0145]
[0146]
[0147]
Table 4
[0148]
[0149] <Preparation of Evaluation Substrate 1>
[0150] In the circuit substrate produced as described above, for the substrate in which the design value of the opening diameter of the top of the through hole produced under laser conditions 1 to 3 is 20 μm, wet desmear treatment, dry desmear treatment 1 or dry desmear treatment 2 is further performed under the following conditions, and the substrate that has not been subjected to desmear treatment is used as evaluation substrate 1.
[0151] (Wet desmear treatment)
[0152] The circuit board prepared as above was immersed in a swelling solution consisting of a mixed solution of Swelling Dip Securiganth P (manufactured by Atotech, 500 ml / l) and 48% sodium hydroxide (4.1 ml / l) at 60°C for 5 minutes. Then, it was immersed in a roughening solution consisting of a mixed solution of Concentrate Compact CP (manufactured by Atotech, 600 ml / l) and 48% sodium hydroxide (55.3 ml / l) at 80°C for 20 minutes, and finally, it was immersed in a neutralizing solution consisting of Reduction Securiganth P500 (manufactured by Atotech, 100 ml / l) and 96% sulfuric acid (35.7 ml / l) at 40°C for 5 minutes to perform a desmear treatment.
[0153] (Dry desmear treatment 1: vacuum plasma etching treatment)
[0154] The circuit substrate prepared above was placed in a vacuum plasma etching device. 2 / CF 4 =25 / 75 volume ratio atmosphere, plasma etching was performed at 100 Pa for 5 minutes.
[0155] (Dry desmear treatment 2: atmospheric pressure plasma etching treatment)
[0156] The circuit substrate prepared above was placed in a flow 2 After that, a gas having a volume ratio of Ar / Ar=10 / 90 was added, and atmospheric pressure plasma etching was performed under the conditions of a radio frequency power of 700 W and a scanning rate of 40 mm / sec.
[0157] <Preparation of Evaluation Substrate 2>
[0158] Among the evaluation substrates 1 prepared as described above, the substrate prepared under the laser condition 3 was subjected to electroless plating and electrolytic plating under the following conditions to serve as the evaluation substrate 2 .
[0159] (Electroless copper plating)
[0160] Among the evaluation substrates 1 subjected to various desmear treatments, the substrate produced under laser condition 3 was subjected to electroless copper plating (manufactured by Uemura Industries, Ltd., alkali ion type Pd) to form a copper seed layer of about 0.3 μm thick on the surface of the insulating layer.
[0161] (Electrolytic copper plating)
[0162] The substrate after the electroless copper plating was immersed in a mixed solution of Acid Cleaner FR (manufactured by Atotech, Ltd., 100 ml / l) and 96% sulfuric acid (100 ml / l) at 23°C for 1 minute (acid washing step). Next, it was immersed in 96% sulfuric acid (100 ml / l) at 23°C for 1 minute (acid immersion step), and finally immersed in a mixed solution of copper sulfate (II) pentahydrate (60 g / l), 96% sulfuric acid (125 ml / l), sodium chloride (70 mg / l), Basic Leveler Cupracid HL (manufactured by Atotech, Ltd., 20 ml / l), and Cupracid GS (manufactured by Atotech, Ltd., 0.2 ml / l) at 23°C for 60 minutes (current density 1 A / dm 2 ), electrolytic copper plating was performed to form a copper plating layer (copper sulfate electroplating step). Then, the substrate was dried at 150° C. for 60 minutes using a hot air circulation dryer to obtain an evaluation substrate 2.
[0163] 〔Evaluation of smear after desmear treatment〕
[0164] For each of the desmear treated evaluation substrates 1, smear in the through-holes was evaluated according to the following criteria under the same SEM conditions as in [Evaluation of the opening diameter of the through-holes by SEM]. The evaluation results are shown in Tables 5 to 7. In addition, the evaluation was "◎" or "○", which was considered acceptable.
[0165] (Evaluation criteria for glue residue)
[0166] ◎: The maximum length of the smear is less than 1 μm.
[0167] ○: The maximum length of smear is 1 μm or more and less than 5 μm.
[0168] ×: The maximum length of the smear is 5 μm or more.
[0169] [Evaluation of Arithmetic Mean Roughness Ra of Insulating Layer]
[0170] In the evaluation substrate 1 after each desmear treatment, for the substrate produced under laser condition 3, the arithmetic mean roughness Ra of the insulating layer was measured using a shape measurement laser microscope (VK-X100 manufactured by Keyence Co., Ltd.). The evaluation length for Ra measurement is 3 mm, and 5 points are measured at random as the average value. The arithmetic mean roughness Ra is evaluated according to the following criteria, and the evaluation results are shown in Tables 5 to 7. In addition, if the evaluation is "◎" or "○", it is qualified. In addition, in Tables 5 to 7, the measured values of the arithmetic mean roughness Ra of Examples 13 to 21 are recorded in the lower section.
[0171] (Evaluation criteria of arithmetic mean roughness Ra)
[0172] ◎: Arithmetic mean roughness Ra is 20 nm or more and less than 100 nm.
[0173] ○: Arithmetic mean roughness Ra is 100 nm or more and less than 150 nm.
[0174] ×: The arithmetic mean roughness Ra is 150 nm or more.
[0175] [Adhesion Evaluation]
[0176] Two cuts were made vertically and horizontally on the copper-plated layer of the evaluation substrate 2 to draw a rectangle with a width of 10 mm (short side) and a length of 60 mm (long side). The short side of the copper-plated layer defined as a rectangle by the cut was peeled off, and the peeled portion was grasped with a clamp. The copper-plated layer of 35 mm in length was peeled off from the insulating layer at an angle of 90 degrees and a speed of 50 mm / min using a desktop tensile tester (EZ-SX manufactured by Shimadzu Corporation) to measure the peel strength (N / cm). The adhesion was evaluated according to the following criteria, and the evaluation results are shown in Tables 5 to 7. In addition, if the evaluation is "◎" or "○", it is qualified. In addition, in Tables 5 to 7, the measured values of the peel strength of Examples 13 to 21 are recorded in the lower section.
[0177] (Evaluation criteria for adhesion)
[0178] ◎: Peel strength is 5.0 N / cm or more.
[0179] ○: The peel strength is 2.5 N / cm or more and less than 5.0 N / cm.
[0180] ×: The peel strength is less than 2.5 N / cm.
[0181] [Determination of manganese content in insulating layer]
[0182] In the evaluation substrate 1 after each desmear treatment, about 50 mg of the insulating layer was cut from the substrate produced under laser condition 3 with a cutter, and the manganese content was measured by ICP emission analysis under the following conditions. The manganese content was evaluated using the following criteria, and the evaluation results are shown in Tables 5 to 7. In addition, if the evaluation is "◎" or "○", it is qualified. In addition, in Tables 5 to 7, the measured values of the manganese content of Examples 13 to 21 are recorded in the lower section.
[0183] Measurement device: 720ICP-OES manufactured by Agilent Technologies
[0184] Measurement conditions: After weighing the sample, put it into 100 ml of ultrapure water and boil it for 30 minutes, then apply ultrasonic waves for 30 minutes. Filter the liquid, measure the volume, and then quantify the amount of manganese using an ICP device.
[0185] (Evaluation criteria for adhesion)
[0186] ◎: Manganese content is less than 10 ppm.
[0187] ○: The manganese content is 10 ppm or more and less than 50 ppm.
[0188] ×: The manganese content is 50 ppm or more.
[0189]
Table 5
[0190]
[0191]
Table 6
[0192]
[0193]
[0194]
Table 7
[0195]
[0196] Description of Figure Numbers
[0197] 1: Circuit board
[0198] 2: Base material
[0199] 3: Insulation layer
[0200] 4: Through hole
[0201] Φt: Diameter of the top opening of the through hole
[0202] Φb: Diameter of the bottom opening of the through hole
Claims
1. A circuit substrate comprising an insulating layer having a through hole formed therein, characterized in that: The insulating layer is composed of a cured product of a thermosetting resin composition, wherein the thermosetting resin composition comprises a thermosetting resin and an inorganic filler. The opening diameter of the top of the through hole is 30 μm or less, The manganese content of the insulating layer is less than 50 ppm.
2. The circuit substrate according to claim 1, wherein: The copper plating layer is formed on at least a portion of the insulating layer, and the peel strength between the insulating layer and the copper plating layer is greater than or equal to 2.5 N / cm.
3. The circuit substrate according to claim 1 or 2, wherein: The arithmetic mean roughness of the insulating layer is less than 150 nm.
4. The circuit substrate according to claim 1 or 2, wherein: The opening diameter of the top of the through hole is 20 μm or less.
5. The circuit substrate according to claim 1 or 2, wherein: The thermosetting resin includes polyphenylene ether.
6. A method for manufacturing a circuit substrate, the circuit substrate comprising an insulating layer, characterized in that: Include: The step of irradiating the insulating layer with a pulse laser having a wavelength of not less than 200 nm and not more than 400 nm and a pulse width of not more than 20 nanoseconds at an output power of not less than 0.3 W to form a through hole; A step of performing copper plating on the through hole without performing a wet desmear process using a strong oxidant to form a copper plated layer.
7. The method for manufacturing a circuit substrate according to claim 6, wherein: The pulse width of the pulse laser is less than 1 nanosecond.
8. The method for manufacturing a circuit substrate according to claim 6 or 7, wherein: The wavelength of the pulse laser is less than 300 nm.
9. The method for manufacturing a circuit substrate according to claim 6 or 7, wherein: A dry desmear process is performed between the step of forming the through hole and the step of forming the copper plating layer.
10. The method for manufacturing a circuit substrate according to claim 6 or 7, wherein: The copper plating layer is formed on at least a portion of the insulating layer, and the peel strength between the insulating layer and the copper plating layer is greater than or equal to 2.5 N / cm.
11. The method for manufacturing a circuit substrate according to claim 6 or 7, wherein: The arithmetic mean roughness of the insulating layer is less than 150 nm.
12. The method for manufacturing a circuit substrate according to claim 6 or 7, wherein: The opening diameter of the top of the through hole is 30 μm or less.
Citation Information
Patent Citations
Manufacture of printed wiring board
JP1997107167A
Method of manufacturing printed wiring board
JP2005294873A